The contribution of Manuel Heleno to the knowledge of the funerary megalithic in Alentejo - Rocha, Leonor (2014)
The excavations conducted by Prof. Manuel Heleno in funerary megalithic monuments in the Central Alentejo, in the 30´s, during the twentieth century, were considered for decades the key to the knowledge of its evolution. This mythical idea naturally originated from the fact that this researcher never published his work.In fact, a review of his fieldwork, conducted recently by the signatory, helped confirm that despite the invaluable contribution that his research represents, the data collected did not unveil the genesis and evolution of the megalithic architecture. With this work we seek to present his main ideas by comparing them with the results of more recent studies, based on work performed by the signatory and by other researchers.